Structural characterization and activation of nature’s fuels of life - van Outersterp, Rianne (Student Undergraduate Research E-journal!, 2016)
Hydrolysis of nucleotide triphosphates (NTPs) is known to drive highly important cellular processes. Of these NTPs, adenine triphosphate (ATP) is mainly studied as it is concerned to be the central fuel of living cells. Gas-phase studies have been performed to elucidate the conformational preference of NTPs focusing on the dependence of the nucleobase and extent of deprotonation. Therefore, a combination of infrared (IR) spectroscopy and mass spectrometry has been applied to ATP, CTP and GTP. IR action spectroscopy and supporting theoretical studies showed that the attached nucleobase has little influence on the three-dimensional structure of the phosphate tail. The favorable deprotonation sites of the singly and doubly deprotonated NTPs have been assigned. This can lead to a better explanation of the behavior and selection of NTPs in living cells.